2020
DOI: 10.1038/s41589-020-0628-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for antibiotic action of the B1 antivitamin 2′-methoxy-thiamine

Abstract: The natural antivitamin 2′-methoxy-thiamine (MTh) is implicated in the suppression of microbial growth. However, its mode of action and enzyme-selective inhibition mechanism have remained elusive. Intriguingly, MTh inhibits some thiamine diphosphate (ThDP) enzymes, while being coenzymatically active in others. Here we report the strong inhibition of Escherichia coli transketolase activity by MTh and unravel its mode of action and the structural basis thereof. The unique 2′-methoxy group of MTh diphosphate (MTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…Although we found that the catalytic Lys138 is disordered in the oxidized, inactive state, it becomes ordered upon reduction and activation. It is known for this enzyme, and for many other classes of enzyme, that orbital steering is critical for catalysis, and that small structural changes can lead to large changes in catalytic competence 24,26,27 .…”
Section: Mechanism Of Allosteric Activationmentioning
confidence: 99%
“…Although we found that the catalytic Lys138 is disordered in the oxidized, inactive state, it becomes ordered upon reduction and activation. It is known for this enzyme, and for many other classes of enzyme, that orbital steering is critical for catalysis, and that small structural changes can lead to large changes in catalytic competence 24,26,27 .…”
Section: Mechanism Of Allosteric Activationmentioning
confidence: 99%
“…45 The coordinate and the topology files of the samples were prepared after the hydrogenation of the samples using the tLEaP module of AmberTools21. 46 The force field parameters for TPP were prepared using Antechamber program of AmberTools21 46,47 while the partial charges were obtained from literature 44 . The systems were modeled with a Mg +2 metal ion that anchors the diphosphate group of TPP that has the net charge of −2.…”
Section: Methodsmentioning
confidence: 99%
“…The protonation states of all amino acids were identified with pKa calculations using pKa-ANI 43 in conjunction with the reported protonation states in the literature 44 . The systems were described using Ambers ff14SB force field parameters for proteins.…”
Section: System Preparationmentioning
confidence: 99%
“…11 The potential applications of each of these thiamine antivitamins are discussed. Source: Modified and adopted from Tylicki et al 6 and Rabe von Pappenheim et al 7…”
Section: Thiamine (B 1 ) Antivitaminsmentioning
confidence: 99%
“…Some examples of synthetic thiamine antivitamins include oxythiamine, amprolium, pyrithiamine, and 3-deazathiamine. 6 Recently, a natural antivitamin of thiamine was discovered known as 2′-methoxy-thiamine 7 (Figure 1). The biosynthesis of TPP has been an appealing target for developing antibiotics against bacteria.…”
Section: Introductionmentioning
confidence: 99%